Mental Health Disorders in Students University as a Challenge in Higher Education Era Society 5.0 - Putra, Ade Herdian; Mudjiran, Mudjiran (Universitas Negeri Padang, 2023)
Mental health disorders in students universities can make students uncomfortable living their daily lives. Mental health disorders will also impact the lectures attended by students. Students who experience mental health disorders tend to be uncomfortable and confused in attending lectures it will impact the low learning outcomes obtained by students. Counseling services in tertiary institutions play an important role in helping students deal with mental health disorders. This type of research is quantitative research with descriptive methods. The purpose of this study was to describe mental health disorders experienced by students in West Sumatra Province throughout 2023. The data used in this study were individual counseling results report data at Universitas Negeri Padang counseling center throughout 2023. The data analysis technique used in this study was descriptive statistical analysis. The results of this study showed that of the 26 students who received counseling services, 1 (3.84%) experienced hopelessness in life, 2 (7.69%) experienced anti-social, 15 (57.70%) experienced academic stress, 5 (19.23%) experienced academic anxiety, and three students (11.54%) experienced excessive anxiety about the future. This study also describes the procedures for counseling services in tertiary institutions in dealing with students' mental health disorders.